Giant plancental chorioangioma, case report - Rondón Tapia, Marta (2017)
Placental chorioangiomas are benign vascular tumors and are the most common placental tumors, with a prevalence of 1%. It rarely surpasses 4 - 5 centimeters in length and, when it happens, is referred to as giant chorioangioma. Pregnancies with giant chorioangiomas are associated with maternal and fetal complications, such as severe microangiopathic haemolytic anemia, preterm labor, polyhidramnios, intrauterine growth restriction, thrombocytopenia and hydrops. A case of giant chorioangioma diagnosed at 22 weeks is presented. Despite close follow-up, delivery occurred at 30 weeks of pregnancy due to polyhidramnios and premature rupture of membranes. Both mother and newborn recovered without complications.